Pembatasan Usia Perkawinan (Tinjauan Undang-undang dan Maqashid asy-Syari’ah) - Elkhairati Elkhairati (Institut Agama Islam Negeri Curup, 2018)
This article aims to review the Law and Maqashidasy-Syari'ah regarding the age limit of marriage. The literature of Islamic Law (fiqh) does not explicitly specify the minimum age limit for prospective marriages. Over the course of time, the law privides a minimum age of mariage. There is a clear conflict between the fiqh and the laws. According to the ushuliyin (Islamic law experts)view, in order to produce a law or a fatwa law, a mujtahid (legal exciter) should pay attention to maqashidsyari'ah (law-making purposes). Because the shari'ah is revealed to realize the benefit of mankind, including the marriage problem. The main problem of this research is to investigate the minimum age restriction of marriage according to the law and how to view the maqashidasy-shari'ah against the provisions of the law. This research used library method. Based on the analysis, it can be concluded that the limitation of the minimum age of marriage in the law is intended for the benefit of the family and the ability to achieve the purpose of marriage. Thus, it can be said that it is in accordance with the application of the maqashidasy-shari'ah, that is to preserve human benefit at the level of an-nasal hifdz (nurturing offspring).